Positive solutions of eigenvalue problems for a class of fractional differential equations with derivatives - Zhang, X.; Liu, L.; Wiwatanapataphee, B.; Wu, Yong Hong (Hindawi Publishing Corporation, 2012)
By establishing a maximal principle and constructing upper and lower solutions, the existence of positive solutions for the eigenvalue problem of a class of fractional differential equations is discussed. Some sufficient conditions for the existence of positive solutions are established.